Implemensi Literasi Sains Dalam Pembelajaran IPA di Sekolah Dasar - Lisa Novianti Gultom; Nur Azmi Alwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In science learning, scientific literacy has a very important role because it prepares students who are qualified, reliable and able to compete internationally. To be able to create and develop scientific literacy in science learning, teachers need to create learning conditions that involve student activity. The aim of this research is to determine the implementation of scientific literacy in science learning in elementary schools. The methods used in this research are literature review/literature study and field observations and interviews. Data processing and analysis was carried out qualitatively with descriptive explanation. It is known that the results of this research are that the implementation of scientific literacy can develop students' thought patterns and behavior and build human character to care, be responsible for themselves, society, the universe and the problems faced by modern society today. Scientific literacy also has an important role in building the welfare of society now and in the future.